Interação entre conversores chaveados com baixa ondulação e células de combustível - Marquezini, Diego Dias (2007)
This dissertation discusses the interaction between fuel cells and the DC-DC converter just connected across its terminals. For that, it presents a modified algorithm to represent the dynamic behavior of fuel cell stacks as much the current ripple effects from power converters on such cells. PEM type fuel cells (Proton Exchange Membrane) are studied to get a reasonable model of the electrochemical and electric characteristics of the involved phenomena in the generation of electric energy from fuel cells. A T filter is used as interface between the fuel cell and the DC-DC converter. This converter must prevent large current ripples going through the cell terminals as well as keeping constant the power flow between the FC and the link DC to prevent itself of possible current transient. To connect it to the grid it was used a three-phase DC-AC converter to inject or to absorb current from the grid at reduced ripple distortion and to stabilize the DC link voltage. DC current controllers were designed to curb the link DC and AC currents within reasonable limits. Validation of the model was carried out through computer simulation in order to have an evaluation of the control system behavior both for the stack and for the injection and/or absorption of energy. Also, theoretical results with practical data from a fuel stack were compared with respect to the load variation across its terminals.